Bacteriophage therapy of human‐restricted Salmonella species—a study in a surrogate bacterial and animal model. (5th June 2022) - Yadav, V.B.; Nath, G.
Abstract: Salmonella Typhi has been an important human‐restricted pathogen from time immemorial, and unfortunately, the indiscriminate use of antibiotics has induced the emergence of multidrug resistance in S . Typhi. Bacteriophage therapy may be a possible alternative in countering antimicrobial resistance. Therefore, this study was planned to assess the efficacy of bacteriophages in treating acute and chronic S . Typhimurium infection in the mouse as a surrogate model. We isolated bacteriophages against S . Typhimurium and selected three different bacteriophages for the in vivo experiments. The lethal dose of S . Typhimurium was decided for Swiss albino mice, and acute infection was developed. Further, bacteriophage therapy by daily intraperitoneal injection of phage cocktail was given for 14 days. While the chronic carrier state of S . Typhimurium in Swiss albino mice was developed by inoculating intraperitoneally sequential 10‐fold increasing doses of the bacterium. On the successful establishment of carrier state, oral feeding of phage cocktail at a high count was given, which completely cured the carrier state within 7 days of feeding. These experiments confirmed that the phage cocktail could eradicate the S . Typhimurium from the mice in both types of infections, that is acute and chronic. Abstract : Significance and Impact of the Study: The human‐restricted Salmonella Typhi causes not only long‐lasting febrile infection but also causes chronic carriage. Both conditions pose a problem in cure due to the emergence of antibiotic‐resistant strains and biofilm formation. Most importantly, chronic typhoid carriage has been linked with cancer gallbladder in high endemic areas and is a persistent infection source. The present study demonstrates that phage therapy takes care of drug‐resistant bacteria and biofilm states in the chronic carriage and successfully eradicates the infection. Therefore, specific bacteriophage therapy, if implemented, can eradicate typhoid and associated problems from the whole globe since the implicated bacteria are confined to humans only.